The Relationship Between Health Literacy and Health Promotion on Social Media with Efforts to Prevent Type 2 Diabetes Mellitus - Andriyan, Rian; Mahmudah, Afika; Gebremedhin, Tsehay (Media of Health Research, 2025)
Type 2 Diabetes Mellitus is one of the non-communicable diseases with an increasing prevalence in Indonesia. Early prevention becomes a strategic step to reduce the number of new cases, especially through health promotion approaches and increasing public health literacy. This study aims to analyze the relationship between health literacy and health promotion on social media with efforts to prevent Type 2 Diabetes Mellitus. The method used is quantitative with a cross-sectional survey approach involving 250 adult respondents who are active social media users. The instruments used include a health literacy questionnaire, the intensity of health promotion exposure on social media, and indicators of diabetes prevention behaviors. Data were analyzed using Pearson correlation and multiple linear regression tests. The results show that there is a significant positive relationship between health literacy (r = 0.521, p < 0.01) and health promotion on social media (r = 0.438, p < 0.01) with efforts to prevent Type 2 Diabetes Mellitus. These findings indicate the importance of strengthening digital-based health education and improving the community's ability to understand health information to promote healthy behavior. This study recommends optimizing informative and interactive health promotion content on social media as an effective prevention strategy.